The emergence of nonviolent nationalist movement among the tribes of Waziristan in Pakistan - Muhammad Irfan Mahsud (Cogent Social Sciences, 2024)
In the second decade of the 21st century, the emergence of Pashtun Tahafuz (protection) Movement (PTM), among the tribes of Waziristan, rose to talk about the rights of Pashtuns after major military operations against the militants in doing so challenging government policies in the erstwhile tribal areas. The research has thoroughly investigated reasons of the emergence and popularity of PTM, its achievements and political ecosystem. The study has employed new social movement and asymmetric federalism theories. The study has argued that the protracted conflict coupled with government policies of securitization in erstwhile Federally Administered Tribal Areas (FATA) of Pakistan and feeling of discrimination among the Pashtun youth has led to the creation of a pro-Pashtun movement in 2018. The movement has been kept nonviolent, promotes progressive values and provides an alternate platform for the youth to address grievances thus halting their enrollment within militant groups. The paper utilises ethnographic-based data collection tools, such as semi-structured interviews, informal discussions and personal observations to reach its findings.